2001
DOI: 10.1002/pc.10547
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental investigation of cure‐induced microcracking in carbon fiber/bismaleimide cross‐ply laminates

Abstract: Transverse microcracks are present in carbon fiber/bismaleimide (BMI) cros: composite laminates composed of 4, 4′‐bismaleimidodiphenylmethane (BMPM)/diallyl bisphenol A (DABPA) matrices after standard cure and fabrication condit and grow in width upon subsequent postcure. This investigation characterizes cure‐induced microcracking in terms of the critical fundamental macroscopic croscopic, and molecular damage mechanisms and thresholds, and a cure cycle modification that prevents microcrack formation under sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…In contrast to the strong surface chemical changes in the spectra, the center of the laminates did not change significantly even at 170°C except for a strong, broad OH region (3440 cm −1 ) increase in both materials to give a spectrum similar to that of the original surface. This center increase (rather than a decrease) again indicates that the OH decreases at the surface are probably due to extensive oxidative degradation of previously formed alcohols and acids and not crosslinking, as previously suggested 5, 27, 28. The surprising result is the low level of change that is seen in the 1770–1100 cm −1 region of the spectra at the center of the composite when the surface is so heavily degraded.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…In contrast to the strong surface chemical changes in the spectra, the center of the laminates did not change significantly even at 170°C except for a strong, broad OH region (3440 cm −1 ) increase in both materials to give a spectrum similar to that of the original surface. This center increase (rather than a decrease) again indicates that the OH decreases at the surface are probably due to extensive oxidative degradation of previously formed alcohols and acids and not crosslinking, as previously suggested 5, 27, 28. The surprising result is the low level of change that is seen in the 1770–1100 cm −1 region of the spectra at the center of the composite when the surface is so heavily degraded.…”
Section: Resultssupporting
confidence: 61%
“…Figure 3 displays the percentage mass change of the System A BMI composite as a function of the square root of time (hours [1/2] ) at all ageing temperatures over the 7500 h of experiment time. If only one mechanism of oxidation/degradation had been involved the lines would have been simple straight lines 28. As plotted in this figure, only the 250°C line has a significant deviation from a straight line, with a strong change in slope at about 400 h. However, the loss of material is so great after this time that it is obvious that the 250°C ageing temperature is much too high an accelerating temperature for a long‐term study.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The cured BMI resins possess excellent mechanical properties, high temperature stability, excellent electric properties, low water absorption, and so on, their outstanding properties of cured BMI allow BMI resins to be used for multilayer printed circuit boards, electrical insulation, semiconductor industries, advanced composites for the aerospace industry, and structural adhesives [1,2]. However, the cured BMI resins are extremely brittle, during the processing of BMI composites, damages such as microcrack and delamination are always caused by heat, force load, and so on, leading to a significant reduction in strength, stiffness, and stability [3][4][5][6][7][8]. References have been reported that polymeric microcapsules containing healing agent can heal microcracks within polymer matrix to maintain the properties of polymer composites as well as toughen polymer composites [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal cure reactions of BMI systems4–9 and related resin modifications,10–17 and structure–property characterization of BMI and BMI composites, have already been widely studied 17–24. However, conventional thermally cured fabrication has many limitations, such as long curing time, thermal stress and induced shrinkage and microcrack formation, expensive tooling, hazardous chemical volatiles, and size limitations for autoclave processing.…”
Section: Introductionmentioning
confidence: 99%